Serum Alkaline Phosphatase in Free-Ranging Male Moose Alces alces (Linnaeus 1758) of Different Age Groups - Maria A. Perevozchikova; Igor A. Domsky; Yulia A. Berezina; Professor Zhitkov Russian Research Institute of Game Management and Fur Farming, Kirov, Russia; Alexandr V. Economov (Техника и технология пищевых производств)
The moose has good prospects for hunting and game breeding. Peripheral blood indicators can provide information about their health status and adaptive capabilities, as well as non-infectious, infectious, and invasive pathologies. Serum alkaline phosphatase activity is one of the most common clinical biochemical tests in this respect. The study involved blood samples obtained from male moose (n = 75) of four age groups: calves aged 6–7 months, young animals of 18 months old, adults of 2.5–7.5 years old, and adults aged ≥ 8.5 years. The biomaterial sampling was carried out in October – December in the southern taiga subzone, Kirov Region. The blood samples were obtained by cutting the jugular vein (Venae jugularis) immediately after the animal was shot during legal hunting. The blood serum tests involved a semi-automatic biochemical analyzer (Biochem SA High Technology, USA). The alkaline phosphatase activity in male European moose during different periods of ontogenesis demonstrated the following pattern. In the first months of life, the enzyme activity was as high as 222.16 ± 31.14 U/L. This process was typical of intense hydrolysis of organic phosphorus esters, including the exchange of macroergs caused by rapid osteogenesis. At 18 months, the demand for organophosphorus compounds in metabolic processes decreased (46.48 ± 44.09 U/L), as did the role of the enzyme in maintaining homeostasis. In adults of 2.5–7.5 years old, alkaline phosphatase activity dropped to 69.88 ± 11.31 U/L. In 8.5-year-old males, it was as low as 47.34 ± 4.74 U/L. All age groups demonstrated significant differences in alkaline phosphatase activity. Therefore, age had a significant effect on enzyme activity. The study also revealed a certain correlation between alkaline phosphatase activity and body weight. The dynamics of alkaline phosphatase activity in ontogenesis reflected homeostatic changes in the moose body. Indicators of alkaline phosphatase activity can serve as an efficiency marker and an additional criterion in standard selection methods in zootechnical practice.